2021
DOI: 10.3390/cancers13184516
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surgical Therapy in Advanced Thymic Tumors

Abstract: A complete resection of thymic tumors is known to be the most important prognostic factor, but it is often difficult to perform, especially in advanced stages. In this study, 73 patients with advanced thymic tumors of UICC stages III and IV who underwent radical resection were examined retrospectively. The primary endpoint was defined as the postoperative resection status. Secondary endpoints included postoperative morbidity, mortality, recurrence/progression-free, and overall survival. In total, 31.5% of pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Furthermore, the resection status of the tumor may affect the patient's prognosis and a macroscopic complete (R0/R1) was more beneficial to the survival of advanced patients. Markowiak et al found that the median survival time after R2 resection was 25 months, which was significantly shorter than that after R0 or R1 resection (115 months) (28). Also in the current study, we got a similar result that total resection of the primary site was better than partial resection or debulking surgery concerning survival time.…”
Section: B Asupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the resection status of the tumor may affect the patient's prognosis and a macroscopic complete (R0/R1) was more beneficial to the survival of advanced patients. Markowiak et al found that the median survival time after R2 resection was 25 months, which was significantly shorter than that after R0 or R1 resection (115 months) (28). Also in the current study, we got a similar result that total resection of the primary site was better than partial resection or debulking surgery concerning survival time.…”
Section: B Asupporting
confidence: 82%
“…Markowiak et al. found that the median survival time after R2 resection was 25 months, which was significantly shorter than that after R0 or R1 resection (115 months) ( 28 ). Also in the current study, we got a similar result that total resection of the primary site was better than partial resection or debulking surgery concerning survival time.…”
Section: Discussionmentioning
confidence: 99%
“…lungs, vessels) in stage III, en bloc resection of these structures should also be performed, and depending on the extent of tumor infiltration, surgical resection should be performed primarily or after induction therapy. 96,97 Randomized-controlled data regarding neoadjuvant or adjuvant therapy do not exist to date. A consensus decision should be reached by an interprofessional team of thoracic surgeons, oncologists, and radiation therapists.…”
Section: Therapeutic Advances In Neurological Disordersmentioning
confidence: 99%
“…Hyperthermic intrapleural chemotherapy, as well as EPP, may be discussed in case of TET in stage IVa [ 6 ]. Further recommendations in international guidelines regarding surgical resection or the application of HITOC are still lacking [ 29 ].…”
Section: Discussionmentioning
confidence: 99%